Development of alkaline electrochemical characteristics demonstrates soil formation in bauxite residue undergoing natural rehabilitation. (26th November 2017) - Kong, Xiangfeng; Tian, Tao; Xue, Shengguo; Hartley, William; Huang, Longbin; Wu, Chuan; Li, Chuxuan
Abstract: Mining and mineral processing industries have generated a large amount of polymineral wastes, causing the destruction and degradation of huge areas of landscapes at extensive geographical locations. Rehabilitation of these mine waste landscapes is critical to social and economic sustainability of mining and metallurgy operations, such as alumina refineries. The Bayer process to refine alumina generates large amounts of highly alkaline bauxite residues that are hazardous to plant growth. Innovative methodologies are urgently needed to address this economic and environmental challenges, one of which is soil formation from bauxite residues. Mineral weathering appears the prerequisite to the initiation of soil formation and development of functional soil properties in bauxite residue disposal areas. The present study investigated natural changes of mineralogy, zeta potential, isoelectric point, surface protonation, active alkaline groups, and associated implications for rehabilitation of the bauxite residue disposal area. Alkaline calcite, hydrogarnet, and sodalite minerals were slowly transformed or dissolved with declining levels over weathering time. Amorphous and semiamorphous minerals also decreased with a corresponding decrease in specific surface area and sorption sites. Zeta potential curve of fresh residue had steeper slope than those of aged residues. The isoelectric point of fresh residue was significantly higher, but those of aged residues were significantly lower, with a significant decrease of isoelectric point with increasing time. These attributes in mineralogy and electrochemical characteristics such as transformation of alkaline minerals, and decreases of surface protonation and active alkaline groups, may be used to help the assessment of soil formation status in the bauxite residues of different age and associated rehabilitation requirements.